‘Texting, sharing, and mentoring’ as an innovative method of community empowerment based on stingless beekeeping adoption in Gunungkidul, Yogyakarta - Mochammad Sofiyulloh; Dwiko B Permadi; Wahyu Tri Widayanti; Emma Soraya (Balai Penerapan Standar Instrumen Lingkungan Hidup dan Kehutanan (BPPLHK)Manado, 2021)
The purpose of this study is to evaluate the texting, sharing, and mentoring (TSM) method as an innovative method of community empowerment applied in 'Go-Honey' program. This method is mixed offline and online with the use of Whatsapp groups connecting program participants, resource persons, and local mentors. Using the Bloom's Taxonomy approach, this study compares the knowledge level of the 'Go-Honey' program participants implementing TSM with other sitngless beekeeping program participants who use the single-face-to-face (TTM) method as a control. The total participants involved in this study were 20 people, half of whom were female members of 'Go-honey', while the other half were not. Participants were asked questions related to cognitive, affective and psychomotor aspects by direct interviews. Observations were also done on the results of the work performance. The results show that the 'Go-Honey' participants have a higher level of knowledge about stingless beekeeping compared to the control model in these three aspects of knowledge. The results of the Mann Whitney test shows that the cognitive, affective and psychomotor scores are significantly different at 1 % alpha. This method has the potential to be applied after the pandemic ends with the principle of distance learning as long as there is the internet connection and the presence of local mentors.Keywords : Bloom’s Taxonomy, knowledge transfer, Whatsapp Group, gender, blended learning, distance learning